Employee’s Perception on Pre-Retirement Planning and Financial Security: A Case of Kilimani Immigration Office in Zanzibar - Juma, Mwanakhamis Othman; Hamad, Abdalla Ussi (European Journal of Applied Sciences, 2026)
Background: Retirement system is not the same across many countries, Some Public sectors provided old age pension is the primary component of retirement security in a particular country while in other countries individual, company and family sources comprise with older generations mainly be source of supports. The study aims to determine the employee’s perception on pre-retirement planning and financial security (a case of Kilimani immigration office in Zanzibar). Methods: A study uses primary data collected through questionnaire at immigration office located at Kilimani Zanzibar according to sample size of 235. Moreover, correlation analysis was applied to analyze employee’s perception on pre-retirement planning and financial security, this model gives necessary information for answering all three research’s questions. Results: The findings reveal that, perceived trust has greater correlation with pre-retirement planning and financial security compared with perceived altitude and perceived usefulness. This suggests that higher perceived trust is associated with better pre-retirement planning and financial security. Conclusion & Recommendations: The study concluded that the correlation analysis reveals significant relationships among perceived altitude, perceived usefulness, perceived trust, and pre-retirement planning and financial security. The findings suggest that perceptions of altitude, usefulness, and trust are interrelated and collectively influence financial planning and security. The study recommends that; the office should create workshops or seminars explaining the benefits of pre-retirement planning. Explain how it helps employees achieve their retirement goals, such as maintaining their desired lifestyle, traveling, or pursuing hobbies.